Thermofluidic assembly of colloidal crystals - Quinn, Desmond; Cichos, Frank (Frontiers in Nanotechnology, 2023)
Colloidal crystals are interesting as functional structures due to their emergent photonic properties like photonic stop bands and bandgaps that can be used to redirect light. They are commonly formed by a drying process that is assisted by capillary forces at the drying fronts. In this manuscript, we demonstrate the optically induced dynamic thermofluidic assembly of 2D and 3D colloidal crystals. We quantify in experiment and simulation the structure formation and identify thermo-osmosis and temperature induced depletion interactions as the key contributors to the colloidal crystal formation. The non-equilibrium nature of the assembly of colloidal crystals and its dynamic control by laser-induced local heating promise new possibilities for a versatile formation of photonic structures inaccessible by equilibrium processes.